2013
DOI: 10.1128/iai.00365-13
|View full text |Cite
|
Sign up to set email alerts
|

The Mycoplasma gallisepticum Virulence Factor Lipoprotein MslA Is a Novel Polynucleotide Binding Protein

Abstract: Although lipoproteins of mycoplasmas are thought to play a crucial role in interactions with their hosts, very few have had their biochemical function defined. The gene encoding the lipoprotein MslA in Mycoplasma gallisepticum has recently been shown to be required for virulence, but the biochemical function of this gene is not known. Although this gene has no significant sequence similarity to any gene of known function, it is located within an operon in M. gallisepticum that contains a homolog of a gene prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…MBOVPG45_0310 and its orthologues in most members of the M. hominis and M. pneumoniae phylogenic clusters lie within a putative nucleotide transporter operon (12,13,16,29,30), and the nuclease activity has been demonstrated for M. agalactiae MAG_5040 (16), M. gallisepticum MGA_0676 (13), M. hyopneumoniae mhp379 (12), M. pneumoniae MPN133 (15), and M. genitalium MG186 (14). It has recently been demonstrated that MslA, the MBOVPG45_0311 homologue in M. gallisepticum, binds single-and double-stranded DNA, suggesting that it may act in concert with these nucleases, with MslA binding and delivering oligonucleotides to the exonuclease, which then processes the oligonucleotides to generate individual nucleotides for transport into the cell via the ABC transporter (13).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MBOVPG45_0310 and its orthologues in most members of the M. hominis and M. pneumoniae phylogenic clusters lie within a putative nucleotide transporter operon (12,13,16,29,30), and the nuclease activity has been demonstrated for M. agalactiae MAG_5040 (16), M. gallisepticum MGA_0676 (13), M. hyopneumoniae mhp379 (12), M. pneumoniae MPN133 (15), and M. genitalium MG186 (14). It has recently been demonstrated that MslA, the MBOVPG45_0311 homologue in M. gallisepticum, binds single-and double-stranded DNA, suggesting that it may act in concert with these nucleases, with MslA binding and delivering oligonucleotides to the exonuclease, which then processes the oligonucleotides to generate individual nucleotides for transport into the cell via the ABC transporter (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that MslA, the MBOVPG45_0311 homologue in M. gallisepticum, binds single-and double-stranded DNA, suggesting that it may act in concert with these nucleases, with MslA binding and delivering oligonucleotides to the exonuclease, which then processes the oligonucleotides to generate individual nucleotides for transport into the cell via the ABC transporter (13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations